Translation Elongation Factor 1-Alpha Interacts Specifically with the Human Immunodeficiency Virus Type 1 Gag Polyprotein - Cimarelli, Andrea (American Society for Microbiology, 1999)
Human immunodeficiency virus type 1 (HIV-1) gag-encoded proteins play key functions at almost all stages of the viral life cycle. Since these functions may require association with cellular factors, the HIV-1 matrix protein (MA) was used as bait in a yeast two-hybrid screen to identify MA-interacting proteins. MA was found to interact with elongation factor 1-alpha (EF1α), an essential component of the translation machinery that delivers aminoacyl-tRNA to ribosomes. EF1α was then shown to bind the entire HIV-1 Gag polyprotein. This interaction is mediated not only by MA, but also by the nucleocapsid domain, which provides a second, independent EF1α-binding site on the Gag polyprotein. EF1α is incorporated within HIV-1 virion membranes, where it is cleaved by the viral protease and protected from digestion by exogenously added subtilisin. The specificity of the interaction is demonstrated by the fact that EF1α does not bind to nonlentiviral MAs and does not associate with Moloney murine leukemia virus virions. The Gag-EF1α interaction appears to be mediated by RNA, in that basic residues in MA and NC are required for binding to EF1α, RNase disrupts the interaction, and a Gag mutant with undetectable EF1α-binding activity is impaired in its ability to associate with tRNA in cells. Finally, the interaction between MA and EF1α impairs translation in vitro, a result consistent with a previously proposed model in which inhibition of translation by the accumulation of Gag serves to release viral RNA from polysomes, permitting the RNA to be packaged into nascent virions.